Data transmission with Simulink on 6-DoF platform on CAN BUS - V. G. Mikhailov (Системный анализ и прикладная информатика)
Use of CAN BUS for data transmission in Real-Time mode with Simulink on control objects is considered (6-DoF a platform).It is revealed that software of CAN_ API.dll adapters, created in the Microsoft Visual Studio (MVS) does not work with TDM-GCC-64 Matlab/Simulink because of different approach in names of the dll functions according to the standard C ++ 11/17. Recompile by the developer of the adapter of its software (dll) in the TDM-GCC-64 environment under Windows is required.It is established that CAN BUS considerably reduces modeling speed by 4.5 times. The way of information compression and fall forward of exchange twice due to byte-by-byte entering of two float values in the data field is offered. Use of identical values of identifiers is applied to two cylinders 6-DoF of a platform and the subsequent their division in the program microcontrollers of cylinders.For implementation of a Real-Time mode in addition to compression it is offered to transfer data with the smaller frequency (quantization) by what a modeling clock period. It was considered that 6-DoF platforms reproduce frequency band to 10–12 Hz. The program of transfer/data exchange with Simulink on stand control devices with quantization is developed. Influence of parameter of quantization for the period of modeling is investigated. It is established that the Real-Time mode of modeling is provided in the range of parameters of quantization (chc=1/350–1/1000). Frequency of exchange with 6 cylinders at the same time corresponds to 230, 150 Hz.